Dynamic Bioinks to Advance Bioprinting. Issue 15 (26th February 2020) - Morgan, Francis L. C.; Moroni, Lorenzo; Baker, Matthew B.
Abstract: The development of bioinks for bioprinting of cell‐laden constructs remains a challenge for tissue engineering, despite vigorous investigation. Hydrogels to be used as bioinks must fulfill a demanding list of requirements, mainly focused around printability and cell function. Recent advances in the use of supramolecular and dynamic covalent chemistry (DCvC) provide paths forward to develop bioinks. These dynamic hydrogels enable tailorability, higher printing performance, and the creation of more life‐like environments for ultimate tissue maturation. This review focuses on the exploration and benefits of dynamically cross‐linked bioinks for bioprinting, highlighting recent advances, benefits, and challenges in this emerging area. By incorporating internal dynamics, many benefits can be imparted to the material, providing design elements for next generation bioinks. Abstract : Bioprinting provides a way to create spatially defined 3D objects for tissue engineering, yet de novo materials design for this application remains a challenge. Recent results show that bioinspired reversible and dynamic hydrogels provide benefits to both the printing process and the maturation of tissue. This review summarizes the emerging dynamic bioinks, outlines challenges, and provides perspective for the future.